Research and Development of the Composition and Technology Receving of Granules of Omeprazol in the Fluid Bed Apparatus - N. V. Mazova; A. L. Marchenko; I. E. Smehova (Разработка и регистрация лекарственных средств, 2019)
Introduction. In this research is devoted to questions of development of structure and technology of granules of an omeprazole. It is established that the most optimal dosage form for medicines of inhibitors of a proton pump is considered to be the tablet with a multiple-unit pellets system (microparticles). In this case of the production of these medicines in the microgranules of a particle are covered with several protective covers. For development of microgranules of an omeprazole is offered the technology of lamination in the fluid bed apparatus.Aim. To receive in the fluid bed apparatus of the microgranules of an omeprazole covered with the enteric cover.Materials and methods. To solve this problem technical characteristics on the granulates of an omeprazole received at various operating modes of the fluid bed apparatus are defined such as form of granules, fractional structure and bulk density are determined by the methods described by the State Pharmacopeia of the XIII edition.Results and discussion. As a result of a research the choice of polymers for layered deposition in the granulation process of a substance of omeprazole is substantiated. Produced selection of enteric polymer of various firms of producers is made for providing a necessary profile of release of an omeprazole in a human body. A copolymer of methacrylic acid – Kollicoat MAE 100 P is chosen. Special attention is paid to receiving the enteric granules of an omeprazole of the correct spherical form with minimum roughness and the improved flowability for further tabletting. For the purpose of receiving granules of an omeprazole of a spherical form selection of an optimum operating mode of the device of a fluid bed apparatus is made for implementation of process of applying the enteric polymer. Following the results of experiments the dependence of quality of fractional structure and appearance of granules of an omeprazole on temperature, pressure and feed rate of polymer is defined. Besides, it is established that the uniformity of application and thickness of a layer of the applied enteric polymer on granules of an omeprazole depend not only on the polymer feed rate, but also on the size of drops of the feed solution.Conclusion. It is established that the quality of the granules of an omeprazole received the enteric polymer was affected by such factors of technological parameters of the fluid bed apparatus as: temperature of the entering air in the apparatus, the air pressure upon a nozzle, air pressure upon a gas-distributing grid of the apparatus, speed of the given polymer, a lot of loading of granules, air temperature of a layer of granules, duration of drying of granules upon termination of process of application of the enteric polymer.